KEPOLIMAKNAAN - Asep Wawan Jatnika (Jurnal Sosioteknologi, 2008)
An ambiguous sentence is a sentence which has more than one possible meaning. In Bahasa Indonesia, an ambiguous sentence can be avoided by (1) putting the hyphen (-) within the phrase that is being referred to, (2) placing the word "“ in the ambiguous phrase "“ to which it is being referred to the front, (3) placing the word which is being referred to in the beginning of the sentence, (4) modifying or determining the ambiguous phrase, and (5) putting comma within the ambiguous phrase to determine the meaning